Distribution and accumulation of heavy metals in Lake Manzala, Egypt. Issue 1 (1st January 2021) - Mandour, Raafat
ABSTRACT: Lake Manzala is the largest saline lake and the second largest one among all lakes in Egypt. Heavy metals' contamination is the most fundamental kind of contamination around the world, particularly in Lake Manzala. The purposes of this paper are investigating the relationship between contents of some heavy metals and major oxides of the Quaternary sediments of Lake Manzala islands as well as the correlation coefficient factor among them.Ten samples of both water and superficial bottom sediments had been representing the lake Manzala through summer, 2019 is covering the sources of pollution to carry out this study. Six heavy metals estimated to assess the environmental risk. The elements were analyzed through atomic absorption spectrometer. Concentration of heavy metals Fe> Zn> Pb; Fe> Mn> Zn> Pb> Cu> Cd in water and sediment is recorded within the southern and southeastern parts of the lake. Significant oxides' arrangement is SiO2 > MgO> CaO> Na2 O> A12 O3 > K2 O> Fe2 O3 . Eco-toxicological of heavy metals' contamination was among the bottom sediments of Lake Manzala. Target hazard quotients (THQ) for individual metals are arranged within the order; Zn>Pb> Cu> Cd. Therefore, heavy metals should eliminate from the wastewater to protect the people and the environment.